Supervisory Leadership and Service Quality in Resort Hotels: A Moderated Mediation of Job Satisfaction and Cultural Context - Antonius Iskandar Yahya; Intan Medya Ratna Puri (Politeknik Negeri Bandung, 2025)
This study investigates the interplay between supervisory leadership, job satisfaction, and service quality in resort hotels, specifically examining how cultural attraction functions as a boundary condition. Drawing on Social Exchange Theory and the Substitutes for Leadership framework, we hypothesize that local cultural context alters the mechanism by which leadership influences service delivery. Data were collected from 72 frontline staff in West Java, Indonesia, and analyzed using Hayes' PROCESS Macro (Model 15). The results of this exploratory study reveal a significant moderated mediation effect. Interestingly, while supervisory leadership directly enhances service quality, this direct effect diminishes when cultural attraction is high. Instead, in culturally rich environments, leadership influences service quality primarily indirectly by facilitating employee job satisfaction. These findings offer a novel theoretical contribution: strong local culture may act as a